2015
DOI: 10.1002/gps.4352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychosocial interventions on self‐efficacy of dementia caregivers: a literature review

Abstract: The efficacy of the interventions for self-efficacy and other outcomes for caregivers and PWD were explored. Recommendations on the effects and significance of various psychosocial interventions for caregivers of PWD in enhancing self-efficacy were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 49 publications
(104 reference statements)
1
41
0
Order By: Relevance
“…The findings indicated that this programme improved CSE of the caregivers, particularly, in the domain of responding to disruptive behaviours. Our study findings are in line with a review that found that CSE could be improved by the interventions that provide knowledge, skill building, information, case management, and emotional management for dementia caregivers . However, it is important to note that this programme constituted eight 60‐minute sessions, while Tang and Chan recommended six 90‐ to 120‐minute sessions to effectively enhance CSE …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The findings indicated that this programme improved CSE of the caregivers, particularly, in the domain of responding to disruptive behaviours. Our study findings are in line with a review that found that CSE could be improved by the interventions that provide knowledge, skill building, information, case management, and emotional management for dementia caregivers . However, it is important to note that this programme constituted eight 60‐minute sessions, while Tang and Chan recommended six 90‐ to 120‐minute sessions to effectively enhance CSE …”
Section: Discussionsupporting
confidence: 86%
“…Our study findings are in line with a review that found that CSE could be improved by the interventions that provide knowledge, skill building, information, case management, and emotional management for dementia caregivers. 44,45 However, it is important to note that this programme constituted eight 60-minute sessions, while Tang and Chan recommended six 90-to 120-minute sessions to effectively enhance CSE. 44 This programme not only enhanced CSE but also encouraged dementia caregivers to search for positive aspects of providing care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 4 articles provided reviews of dyadic interventions (involving caregiver and CR together) [39,40,55,60] while 15 covered technology-based (e.g, telephone, internet) interventions [17,22,25,26,28,30,41,42,46,51,54,57,62,64,68]. In addition, 12 "miscellaneous" reviews covered themes that cannot be classified into any of the above categories (e.g., counseling merged with case management, and interventions targeting resilience or grief) [12,18,19,22,40,44,52,53,61,67,70,71]. Two provided general overviews [35,69].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the 43 reviews that analyzed burden (including measures of overload, stress and behavioral bother), over half (k = 28) provided support for intervention effects. Burden was found to be reduced by psychoeducation [12,34,37,51,53,58,66], counseling/psychotherapy [12,32,36,53] OT interventions, [16], mindfulness-based interventions [21,33,38], communication training [47], respite/ day care [12,63], home support [20], care coordination/ case management [15,53], physical activity interventions [50], multicomponent interventions [14,31], dyadic interventions [39], technology-based interventions [17,28,46,51,54], and miscellaneous or intervention programs in general [12,19,35,53,61].…”
Section: Burdenmentioning
confidence: 99%